Late Quaternary lake evolution in the Gaxun Nur basin, central Gobi Desert, China, based on quartz OSL and K‐feldspar pIRIR dating of paleoshorelines. (23rd February 2017) - Li, Guoqiang; Li, Fangliang; Jin, Ming; She, Linlin; Duan, Yanwu; Madsen, David; Wang, Leibin; Chen, Fahu
ABSTRACT: Paleoenvironmental changes in the Gobi Desert of Mongolia are of global significance because fluvial and lacustrine deposits in the region constitute one of the dominant sources of Northern Hemisphere dust. A series of well‐preserved geomorphic shoreline features at different elevations around the Gaxun Nur basin, central Gobi Desert, indicate past fluctuations of the basin's terminal lake. We measured the exact elevation of shorelines in the basin using a Differential Global Positioning System, and found six shorelines at ∼24, ∼20, ∼18, ∼16, ∼15 m and ∼8 m above the modern basin floor. Quartz optically stimulated luminescence and K‐feldspar post‐infrared infrared stimulated luminescence methods were used to date these shoreline features. The reliability of the dates was confirmed using internal checks of luminescence characteristics and by comparing the quartz and K‐feldspar ages. Our results suggest a lake developed in the Gaxun Nur basin by at least ∼121 ka. Lake levels increased from ∼8 to ∼24 m from ∼121 to ∼85 ka. A 20–13‐m‐deep lake again formed in the basin between ∼8.4 and 0.8 ka. Monsoonal precipitation and temperature variations during Marine Isotope Stage 5 and the mid–late Holocene were the likely causes of paleolake formation and lake level fluctuations.